2014
DOI: 10.1093/carcin/bgt493
|View full text |Cite
|
Sign up to set email alerts
|

The activation of P2Y2 receptors increases MCF-7 breast cancer cells migration through the MEK-ERK1/2 signalling pathway

Abstract: Adenosine 5'-triphosphate (ATP) is found in high concentrations in the extracellular microenvironment of tumours and is postulated to play critical roles in cancer progression. In the present study, we found that stimulation of human MCF-7 breast cancer cells with 30 µM ATP increased their migration by 140 ± 31%, whereas it had minor or no effect on their proliferation. This effect was prevented by the ectonucleotidase apyrase and was antagonized by suramin and pyridoxalphosphate-6-azophenyl-2',4'-disulfonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 54 publications
2
56
0
2
Order By: Relevance
“…In addition, considering that apyrase exerted slightly stronger inhibitory effect on TGF-β1-induced migration than A438079, it is possible that other P2 receptor, other than P2X7, could be partly involved in TGF-β1-induced ATP-dependent migration of H292 cells. For example, it has been reported that activation of P2Y2 receptor also increases cell motility in breast cancer cells [23]. Taken together with our previous report of involvement of ATP-P2X7 signaling in TGF-β1-induced cell migration of A549 cells [17], it is possible that involvement of autocrine signaling mediated by release of ATP and activation of P2X7 receptor is a distinctive feature of cancer cell migration.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, considering that apyrase exerted slightly stronger inhibitory effect on TGF-β1-induced migration than A438079, it is possible that other P2 receptor, other than P2X7, could be partly involved in TGF-β1-induced ATP-dependent migration of H292 cells. For example, it has been reported that activation of P2Y2 receptor also increases cell motility in breast cancer cells [23]. Taken together with our previous report of involvement of ATP-P2X7 signaling in TGF-β1-induced cell migration of A549 cells [17], it is possible that involvement of autocrine signaling mediated by release of ATP and activation of P2X7 receptor is a distinctive feature of cancer cell migration.…”
Section: Discussionsupporting
confidence: 76%
“…Apart from influencing cellular proliferation, extracellular ATP was demonstrated by our group to promote invasion of prostate cancer cells by activating Rho GTPase and upregulating MMPs . Chadet S and colleagues found that ATP enhanced the migration of human MCF‐7 breast cancer cells, but it exhibited minor or no effect on tumor cellular proliferation . In this study, we found that ATP inhibited the proliferation of MCF‐7 and MDA‐MB‐231 cells, but promoted tumor cells' migration and invasion.…”
Section: Discussionsupporting
confidence: 48%
“…Subsequently, we revealed that P2Y2, a preferred receptor for ATP, stimulated the invasion of prostate cancer cells by enhancing EMT process . Chadet and colleagues found that P2Y2 receptor increases MCF‐7 breast cancer cell migration by activating MEK‐ERK1/2 signaling pathway . Using xenograft tumor model, Jin H and colleagues found that the highly metastatic breast cancer cells MDA‐MB‐231 released higher levels of ATP and showed a higher P2Y2 activity compared with the lowly metastatic breast cancer cells MCF‐7.…”
mentioning
confidence: 99%
“…Indeed, we demonstrated that the pharmacological inhibition of P2Y6 resulted in a reduction in the cellular migration of mesenchymal‐like MDA‐MB‐231 breast cancer cells. In this context it is interesting to note that P2Y2 was recently shown to regulate the migration of human hepatocellular carcinoma cells (Xie et al., 2014), prostate cancer cells (Li et al., 2013) and MCF‐7 breast cancer cells (Chadet et al., 2014). The role of P2Y6 in hypoxia‐induced vimentin expression in MDA‐MB‐468 cells and in MDA‐MB‐231 cell migration, the elevation of P2Y6 in basal‐like breast cancers and breast cancers with lower overall survival, collectively identify P2Y6 as a potential therapeutic target for breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%